Structural and Superconducting Properties of Tungsten Hydrides Under High Pressure - Zheng, Shuang; Zhang, Shoutao; Sun, Yu; Zhang, Jing; Lin, Jianyan; Yang, Guochun; Bergara, Aitor (Frontiers in Physics, 2018)
Unveiling the relation between crystal structure and superconductivity of hydrides becomes a fascinating research area in chemistry and condensed-mater physics. Although much efforts have been made to study chemical reaction between tungsten and hydrogen, the crystal structures, superconductivity, and phase diagram of tungsten hydrides under high pressure have not been fully explored and built thus far. In this work, we carried out extensive structural search on W-H binary compounds through first-principles swarm-intelligence structural search calculations. Besides reproducing the known W-H compounds, a new stoichiometry WH5 with P6mm symmetry becomes stable above 230.2 GPa. Intriguingly, P6mm WH5 shows a critical temperature (Tc) value of 60.8 K, which is much higher than 31.6 K in WH6. This finding is different from the knowledge of compounds with higher H content exhibiting higher Tc, which might be attributed to the appearance of unique H network and tetrahedron H units in WH5. Electronic property and superconductivity of the other tungsten hydrides are also investigated. The built pressure-composition phase diagram provides some useful information for experimental synthesis.